The philosophical turn: examining the foundational presuppositions of international relations theory and the potential for an alternative image of the state - Wright, Richard Ian (Fakulti Sains Sosial dan Kemanusiaan, Universiti Kebangsaan Malaysia, 2019)
Mainstream International Relations theory (neorealism, neoliberalism and positivist constructivism) largely adheres to a model of the state as a rational unitary-actor. This model is deemed necessary because the goal of the mainstream theories is to isolate the systemic causes of international state behavior. This goal is predicated upon certain underlying philosophical presuppositions, namely: 1) the privileging of material over ideational causes, and 2) the analytical distinction between state and international levels of analysis. The first presupposition leads to a focus on material forces (e.g. weapons and economic resources), largely excluding the impact of ideas. The second presupposition isolates systemic forces, bracketing-out the internal domestic politics of states types of government for example. This focus on material and systemic forces is facilitated by the rational unitary-actor image of the state. However, if the goal is to understand alternative causal factors (e.g. individual agency, domestic politics, multi-level shared idea for example) then an alternative model of the state becomes necessary. The model proposed here is one based upon Weber’s methodological individualism and views the state as a “pluralistic” (rather than unitary) and “fallible” (rather than rational) international actor.